Inactivation efficiency of slightly acidic electrolyzed water against microbes on facility surfaces in a disinfection channel - Yitian, Zang; Baoming, Li; Zhengxiang, Shi; Xiaowei, Sheng; Hongxiang, Wu; Dengqun, Shu (International Journal of Agricultural and Biological Engineering, 2017)
Slightly acidic electrolyzed water (SAEW, pH 6.0-6.5) is an ideal and environmentally-friendly disinfectant, which was used to prevent and control bacterial infections on farms. This work aims to investigate the inactivation effectiveness of SAEW in inactivating microbes in a disinfection channel. The bactericidal efficiency of SAEW on equipment surfaces was compared to two commercial disinfectants, Kuei A bromide solution (KAS, 5:1000 vol/vol) and Glutaraldehyde solution (GS, 5:1000 vol/vol). The disinfection effectiveness of SAEW in inactivating Salmonella enteritidis (S. enteritidis) on equipment surfaces in the disinfection channel was evaluated, and a model was developed using multiple linear regression analysis. Results indicated that SAEW was significantly (p<0.05) more efficient than KAS and GS on kits and clothing in the disinfection channel at 1 min. The SAEW did not contribute as aggressively to respiratory difficulty as KAS and GS. Maximum reductions of 2.362 log10 CFU/cm2, 2.613 log10 CFU/cm2 and 2.359 log10 CFU/cm2 for Salmonella enteritidis were obtained from clothing surfaces, iron materials, and kits treated with SAEW for 2.5 min at a chlorine concentration of 220 mg/L. Moreover, the established model had a good fit-quantified by the determination coefficient R2 (0.939) and a lack of fit test (p>0.05). In addition, available chlorine concentration (ACC) was an important factor than other factors, and the inactivation efficiency of Salmonella enteritidis sprayed by SAEW treatment was different between iron materials, kits and clothing surfaces (iron > kit > clothing).Keywords: slightly acidic electrolyzed water, disinfection channel, S. enteritidis, disinfection, bacterial infection, prevention and control, livestock farmDOI: 10.25165/j.ijabe.20171006.2848Citation: Zang Y T, Li B M, Shi Z X, Sheng X W, Wu H X, Shu D Q. Inactivation efficiency of slightly acidic electrolyzed water against microbes on facility surfaces in a disinfection channel. Int J Agric & Biol Eng, 2017; 10(6): 23–30.